1256. In Vivo Activity and Structural Characterization of a New Generation γ-Lactam Siderophore Antibiotic Against Multidrug-Resistant Gram-Negative Bacteria and Acinetobacter spp. (31st December 2020) - Goldberg, Joel; Bethel, Christopher; Hujer, Andrea M; Marshall, Steven; Taracila, Magdalena A; Papp-Wallce, Krisztina M; Kumar, Vijay; van den Akker, Focco; Plummer, Mark; Bonomo, Robert A
Abstract: Background: Multidrug-resistant (MDR) A . baumannii presents a critical need for innovative antibacterial development. We have identified a new series of γ-lactam (oxopyrazole) antibiotics that target penicillin binding proteins (PBPs) and incorporate a siderophore moiety to facilitate periplasmic uptake. YU253911, an advanced iteration of this class shows potent in vitro activity against clinically relevant Gram-negative organisms including Acinetobacter spp. Methods: Minimum inhibitory concentrations (MICs) for YU253911 were determined using broth microdilution against a 198-member panel of clinical isolates of Acinetobacter spp. Resistant strains were further evaluated for susceptibility to YU253911 in combination with sulbactam. The antibiotic's target protein was evaluated by binding studies with Bocillin™, a fluorescent penicillin analogue, and modeled in the PBP active site. YU253911 was evaluated in vivo in a mouse soft tissue infection model. Results: MIC testing for YU253911 revealed an MIC50 of 0.5 μg/mL and an MIC90 of 16 μg/mL, which compared favorably to all tested β-lactam antibiotics including penicillins, cephalosporins, monobactams and carbapenems (MIC50 = 2 to > 16 μg/mL). Combination with sulbactam augmented the activity of the agent. There was no apparent correlation between YU253911-resistance and the presence of specific β-lactamase genes, and incubation with representative β-lactamase proteins (KPC-2, OXA-23, OXA-24, PER-2, PDC-3, NDM-1, VIM-2, and IMP-1) showed negligible hydrolysis of the agent. YU253911 showed promising preclinical pharmacokinetics in mice with a 15 h half-life from intravenous administration and demonstrated a dose-dependent reduction in colony forming units from 50 and 100 mg/kg q6h dosing in a mouse thigh infection model using P. aeruginosa . Conclusion: YU253911, a new generation γ-lactam antibiotic effective against MDR A. baumannii demonstrated promising in in vitro potency and favorable pharmacokinetics which correlated with in vivo efficacy. Disclosures: Krisztina M. Papp-Wallce, PhD, Entasis (Grant/Research Support)Merck (Grant/Research Support)Venatorx (Grant/Research Support) Robert A. Bonomo, MD, Entasis, Merck, Venatorx (Research Grant or Support)